Penerapan Strategi Everyone is a Teacher Here (ETH) Berbantuan Media Kartu Truth or Dare Untuk Meningkatkan Hasil Belajar Kognitif Pada Materi Bumi dan Tata Surya - Misti, Afifah; Yennita, Yennita; Syahril, Syahril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2025)
Abstrac: This study aims to describe students’ cognitive learning outcomes after the implementation of the Everyone is a Teacher Here strategy assisted by Truth or Dare card media, as well as to identify differences in cognitive learning outcomes between the class using the Everyone is a Teacher Here strategy assisted by Truth or Dare cards and the class that continued to use conventional methods. The research was conducted at MTsN 2 Kuantan Singingi from April to September 2025. The method employed was a quasi-experimental design with a non-equivalent posttest-only control group design. The data were obtained from the posttest results of both classes. Data analysis was carried out using descriptive and inferential statistics. The results showed that the average cognitive learning score of the experimental class was 74.4, categorized as good, while the control class achieved an average score of 63.4, categorized as fair. Inferential analysis using a t-test produced a significance value of 0.001 < 0.05, indicating a significant difference between the experimental and control classes. It can be concluded that the implementation of the Everyone is a Teacher Here strategy assisted by Truth or Dare card media is proven to be effective in improving students’ cognitive learning outcomes. Keywords: Everyone is a Teacher Here (ETH) Strategy, Truth or Dare Card Media, Earth and Solar System Materia